Profit Shifting and Productivity Mismeasurement - Eric J. Bartelsman; Roel Beetsma (Tinbergen Institute, 2000)
This note identifies profit shifting in response to cross-countrydifferences in corporate tax rates as a source of productivitymismeasurement. To quantify the magnitude of mismeasurement, theprofit-shifting effect is isolated from other possible effects ofcorporatetax rates changes on real activity shifts. The empirical illustrationsuggests that the mismeasurement effect is quantitativelysignificant.
Keywords: 330; Verrechnungspreis; Körperschaftsteuer; Produktivität; Messung; Theorie; OECD-Staaten